The Pengaruh Variasi Sudut Kemiringan Pisau terhadap Kapasitas Produksi dan Efisiensi Pemotongan Mesin Pencacah Rumput - Endang Prihastuty; Achmad Tohasan; W. Djoko Yudisworo; Muhamad Faisal; Cucu Adi (Mestro: Jurnal Teknik Mesin dan Elektro, 2026)
Forage is the main component in ruminant farming, but manually chopping grass is considered inefficientin terms of time and effort. This study aims to design and build a grass chopper machine with blade anglevariations of 15°, 30°, and 60°, as well as to find out the effect of each angle on production capacity, thequality of the chopped grass, and cutting efficiency. The machine is designed using a Honda GX160gasoline engine with 5.5 hp, an 8:1 ratio pulley transmission system, a frame made of angle iron, and HSSsteel blades, with machine dimensions of 80 cm long, 45 cm wide, and 101.11 cm high. Testing was carriedout by inserting 3 kg of grass material for each blade angle variation. The test results showed that a 60°blade angle couldn’t be used because it collided with the machine body. A 15° blade angle gave aproduction capacity of 72 kg/hour with a cutting efficiency of 63% and uneven chopping quality.Meanwhile, a 30° blade angle provided the best performance, with the highest production capacity of 90kg/hour, cutting efficiency reaching 66%, and even chopped quality. Based on these results, it wasconcluded that a 30° blade tilt is the most optimal angle to use on a grass chopper machine for producinggood-quality chops more efficiently.